Peripheral nerve diffusion tensor imaging (DTI): normal values and demographic determinants in a cohort of 60 healthy individuals - Kronlage, Moritz; Münch, Véronique; Schwarz, Daniel; Godel, Tim; Uhlmann, Lorenz; Heiland, Sabine; Bendszus, Martin; Bäumer, Philipp (European radiology, 2018)
Objective: To identify demographic determinants of peripheral nerve diffusion tensor imaging (DTI) and to establish normal values for fractional anisotropy (FA), axial diffusivity (AD), radial diffusivity (RD), and mean diffusivity (MD). Methods: Sixty subjects were examined at 3 Tesla by single-shot DTI. FA, AD, RD, and MD were collected for the sciatic, tibial, median, ulnar, and radial nerve and were correlated with demographic variables. Results: Mean FA of all nerves declined with increasing age (r = −0.77), which could be explained by RD increasing (r = 0.56) and AD declining (r = −0.40) with age. Moreover, FA was inversely associated with height (r = −0.28), weight (r = −0.38) and BMI (r = −0.35). Although FA tended to be lower in men than women (p = 0.052), this difference became completely negligible after adjustment to body weight. A multiple linear regression model for FA was calculated with age and weight as predictors (defined by backward variable selection), yielding an R 2 = 0.71 and providing a correction formula to adjust FA for age and weight. Conclusion: Peripheral nerve DTI parameters depend on demographic variables. The most important determinants age and weight should be considered in all studies employing peripheral nerve DTI. Key points • Peripheral nerve diffusion tensor imaging (DTI) parameters depend on demographic variables. • Fractional anisotropy (FA) declines with increasing age and weight. • Gender does not systematically affect peripheral nerve DTI. • The formula presented here allows adjustment of FA for demographic variables.